The Effect Of Green Accounting, Environmental Performance, Company Size, and Sustainability Report On Firm Value In Coal Industry Energy Sector - Lutpiah Nur Azizah; Renny Renny (Universitas Gunadarma, 2024)
Climate change and its negative impact on the environment is becoming an increasingly urgent global issue. Coal-fired power plants are the largest contributor to GHG emissions from the energy sector. Coal industry companies, as one of the industrial sectors that produce greenhouse gas emissions, have an important role in environmental conservation efforts. This study aims to determine the effect of green accounting, environmental performance, company size, and sustainability report on capital structure in coal industry energy sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2023. The type of research used is descriptive research. The data used in this study are secondary data in the form of company annual reports and sustainability reports obtained from the official IDX website (www.idx.co.id) and the official websites of related companies. The data collection method uses the documentation method. The results concluded that green accounting, environmental performance, and sustainability reports have no effect on firm value. Meanwhile, company size affects firm value in coal industry energy sector companies listed on the Indonesia Stock Exchange for the period 2019-2023.